A Million Person Household Survey: Understanding the Burden of Injuries in Bangladesh - Olakunle Alonge (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Ninety percent of lives claimed by injuries occur in low- and middle-income countries. This special issue, A Million Person Household Survey: Understanding the Burden of Injuries in Bangladesh, aims to assess these injuries-including falls, drowning, burns, road traffic injuries - to inform efforts to reduce the burden they cast on millions of people and families in a low income country. This issue offers a unique collection of research on the epidemiology of fatal and non-fatal injuries in Bangladesh. Based on a survey of more than one million people, this research-conducted by the International Injury Research Unit, Department of International Health at the Johns Hopkins Bloomberg School of Public Health and two Bangladesh partners, the Center for Injury Prevention and Research and the International Center for Diarrheal Disease Research, Bangladesh with funding from Bloomberg Philanthropies, was part of a large-scale, population-based, child-drowning prevention project called "Saving of Lives from Drowning in Bangladesh." The project tested the large-scale effectiveness and cost-effectiveness of evidence-based interventions to reduce drowning related deaths for children less than five years of age (reported elsewhere). We hope this data will be useful to researchers, students, practitioners and national decision makers.